Conceptions and practices of health promotion according to dental students in Santa Catarina - Brazil - Luciane Campos; Ricardo Carniel; Gregory Hacke Azambuja; Elisabete Rabaldo Bottan (Universidade de Fortaleza, 2012)
Objective: To investigate conceptions, practices and knowledge expressed by dental students in Santa Catarina, Brazil, concerning health promotion. Methods: This research was a descriptive study with qualitative approach, by means of primary data collection. The target population was composed by dental students in the State of Santa Catarina. The sample consisted of 148 freshmen students and 122 academic graduates. The data was obtained by the application of a semi-structured interview. For analysis, the Content Analysis principles were adopted. Results: The most cited concepts of health promotion by freshmen and seniors were: self-care/quality of life (37.3% and 19.4%), development of personal skills (18.4% and 34.6%), healthy public politics (3.8% and 3.5%), strengthening of community action (7.4% and 7.3%), reorientation of health care services (11.3% and 12.4%), prevention/treatment (21.5% and 23.7%). As health promotion practices, freshmen and seniors cited: development of personal skills (36.2% and 47.1%), prevention/treatment (38.4% and 35.3%), promotion of healthy environments (16.5% and 4.7%), strengthening of community action (6.7% and 6.7%), reorientation of health care services (1.3% and 5.1%) and healthy public politics (0.9% and 1.2%). Conclusion: Part of the subjects expressed concepts and practices of health promotion linked to the curative-preventive action, which is a mistake. However, a significant proportion of the interviewees mentioned concepts and practices accordingly to health promotion, which may indicate a moment of transition, where the biomedical model is gradually being replaced by the model of health promotion.